If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -12 = -1 + -7y Reorder the terms: -12 + -5y = -1 + -7y Solving -12 + -5y = -1 + -7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7y' to each side of the equation. -12 + -5y + 7y = -1 + -7y + 7y Combine like terms: -5y + 7y = 2y -12 + 2y = -1 + -7y + 7y Combine like terms: -7y + 7y = 0 -12 + 2y = -1 + 0 -12 + 2y = -1 Add '12' to each side of the equation. -12 + 12 + 2y = -1 + 12 Combine like terms: -12 + 12 = 0 0 + 2y = -1 + 12 2y = -1 + 12 Combine like terms: -1 + 12 = 11 2y = 11 Divide each side by '2'. y = 5.5 Simplifying y = 5.5
| -5y-12=-1-7 | | 24+y=9t | | 10x^2+21x+8=0 | | 7d-2d+5d-9=2d | | 7500.00+155.00x=92440 | | x+22=5 | | 152=3X | | y+1/2=1-y/3 | | (x+5)(2+x)=0 | | 3W-10-0.5w=31 | | 7500+155=92440 | | 3y/4-3=y/2+2 | | 300+25x=900-25x | | 4+x=2x-6 | | 0.08r-7=0.02r+5 | | x/2=20-x/3 | | x/4-1=x/5 | | 900-25x=300+25x | | 0.2n-9=13 | | 7500+155x= | | 9x+52=12 | | 0=5n+-2n | | 2(4-3)=8x-13 | | 22+x=52 | | 11c-33c^2=0 | | 11(2q-8)=4(7-3q) | | 7xy=z | | 4x-3-6x+2= | | 3(x+2)+4= | | v=34*10 | | x-2x+4= | | x+(x+2)+(x+4)=2x-16 |